Lokalizacja kościołów i cmentarzy we wsiach józefińskich na terenie województw małopolskiego i podkarpackiego - Cepil, Monika (Zeszyty Wiejskie, 2019)
The article presents the results of research on the location of churches and cemeteries in Josephine villages in the Lesser Poland Voivodship and Subcarpathian Voivodship. Detailed analyzes covered selected rural settlement units on a case-study basis. In the first part of the article, aspects of the genesis of the distribution of churches and cemeteries in the study area were examined while extracting the characteristic types of distribution of the analyzed objects. The further part of the study presents the location and distribution of churches and cemeteries in the contemporary landscape of the studied villages.